2022
DOI: 10.1097/md.0000000000030275
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis predicts poor prognosis of Asian patients with colorectal cancer: A systematic review and meta-analysis

Abstract: Background: There is no study analyzing and evaluating the prognostic role of thrombocytosis in Asian patients with colorectal cancer (CRC).Methods: A systematic search of articles (PubMed, Embase, and the Cochrane Library) was performed to identify studies using the terms Platelet count, Thrombocytosis, Thrombocytoses, Thrombocythemia or Thrombocythemias with colon, colonic, rectal, rectum, colorectal and prognostic, prognosis, survival or outcome.Results: Thirteen eligible studies with 3964 patients were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Several studies have indicated that thrombocytosis increases the risk of recurrence and death in various forms of cancer [41] , [42] , [43] , [44] . The proposed underlying mechanism seems to be primarily related to the onset of a cancer-induced inflammatory cascade that triggers the release of several inflammatory factors which, in turn, promote cancer progression by enhancing malignant conversion, invasion and metastasis [4] .…”
Section: Commentmentioning
confidence: 99%
“…Several studies have indicated that thrombocytosis increases the risk of recurrence and death in various forms of cancer [41] , [42] , [43] , [44] . The proposed underlying mechanism seems to be primarily related to the onset of a cancer-induced inflammatory cascade that triggers the release of several inflammatory factors which, in turn, promote cancer progression by enhancing malignant conversion, invasion and metastasis [4] .…”
Section: Commentmentioning
confidence: 99%
“…D-dimer and brinogen degradation products (FDP) are protein fragments released into the systemic circulation due to degradation of blood clots. Many coagulation abnormalities, such as thrombocytosis, high brinogenemia, elevated D-dimer levels and FDP, are associated with the progression or poor prognosis of CRC [5][6][7] . In addition, many studies have found that the hypercoagulable state of blood is closely related to the metastasis and development of tumors [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytosis is characterised by an elevated platelet count in the bloodstream and can have various physiological and pathological origins. According to the 2017 criteria by the WHO, thrombocytosis is defined as a platelet count above 450×10 9 /L 1. It can occur as a primary event in haematological diseases or as a secondary event known as reactive thrombocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…The increased platelet concentration and aggregation can lead to the consumption of von Willebrand factor, increasing the risk of bleeding or thrombosis 1 3. While secondary thrombocytosis is generally benign, in the presence of iron deficiency, it can pose a risk of arterial and venous thrombosis 5…”
Section: Introductionmentioning
confidence: 99%